ANALISIS PENGARUH BUDAYA KERJA, JAMINAN SOSIAL DAN LOYALITAS KARYAWAN TERHADAP KINERJA DI PT.GARUDA INDONESIA YOGYAKARTA - Chintya Fitri Yulianti (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2014)
This study aims: 1) To determine the effect of work culture on employee performance in PT.Garuda Indonesia Yogyakarta. 2) To determine the effect of Social Security on the performance of employees in PT.Garuda Indonesia Yogyakarta. 3) To determine the effect of loyalty to performance employee in PT.Garuda Indonesia Yogyakarta. 4) To determine the effect work culture, social security and loyalty to performance ticketing staff in PT.Garuda Indonesia Yogyakarta. This study used an explanatory research approach to the 80 respondent, employees of the ticketing operation in PT.Garuda Indonesia Yogyakarta. Sampling was done by using census. Data collection techniques in this study using questionnaire. The data obtained were analyzed quantitatively using analytical tool multiple linear regression.Based on the research result, obtained byregression equation is :Y = 0.175 X1 + 0.852 X2 + X3 0176 . Culture Employment, Social Security and Loyalty affect to performance of the performance ticketing staffin PT.Garuda Indonesia Yogyakarta. Key words: Culture Employment, Social Security, Loyalty, Performance.